Clinical Efficacy of Transurethral Resection of the Prostate Combined with Oral Anticholinergics or Botulinum Toxin – A Injection to Treat Benign Prostatic Hyperplasia with Overactive Bladder: A Case–Control Study - Allameh F; Basiri A; Razzaghi M; Abedi A; Fallah-karkan M; Ghiasy S; Hosseininia SM; Montazeri S (Dove Medical Press, 2020)
Farzad Allameh,1 Abbas Basiri,1 Mohammadreza Razzaghi,2 Amir reza Abedi,3 Morteza Fallah-karkan,2,3 Saleh Ghiasy,3 Seyyed Mohammad Hosseininia,3 Saeed Montazeri3 1Urology and Nephrology Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Laser Application in Medical Sciences Research Center, Shohada-e-Tajrish Hospital, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Department of Urology, Shohada-e-Tajrish Hospital, Shahid Beheshti University of Medical Sciences, Tehran, IranCorrespondence: Saeed MontazeriUrology Resident, Shohada E Tajrish Hospital, Shahid Beheshti University of Medical Sciences, Tehran, IranTel +98 21 22749221Email saeed.montazeri89@gmail.comIntroduction: Recent investigations showed that anticholinergic drugs could use for the management of storage symptoms after transurethral resection of the prostate (TURP). The use of intravesical botulinum toxin-A (BTX-A) for the management of overactive bladder is rapidly increasing. In this research, we assess the efficacy of BTX-A vs solifenacin in men suffering from bladder outlet obstruction–over active bladder (BOO-OAB) managed with TURP.Methods: In this case–control study, 50 men with BOO-OAB randomized into two groups. The control group (A) underwent TURP and subsequently managed by solifenacin 5 mg daily, and the case group (B) underwent TURP and BTX-A injection in the bladder wall in the same session. Treatment success was the primary outcome and defined as post-injection improvement in the storage score of the International Prostate Symptom Score (IPSS) from baseline.Results: The IPSS, post-void residual volume, frequency, incomplete emptying, nocturia and urgency subscores considerably ameliorated after 12 weeks and 36 weeks for both groups, but it was more significant in the case arm. The quality of life (QoL) scores significantly improved after the treatments in both groups. Intervention group showed significant reductions regarding urgency incontinence compared with the solifenacin group at 12th and 36th weeks.Conclusion: BTX-A is an effective and well-tolerated treatment in patients with benign prostatic hyperplasia (BPH) who are candidates of TURP and simultaneously suffer from OAB symptoms.Keywords: anticholinergic drug, benign prostatic hyperplasia, botulinum toxin-A, over active bladder, solifenacin, TURP